DOKUMEN ELEKTRONIK SEBAGAI ALAT BUKTI DALAM PERSIDANGAN PERADILAN PERDATA DIKAITKAN DENGAN UNDANG-UNDANG NOMOR 1 TAHUN 2024 TENTANG INFORMASI DAN TRANSAKSI ELEKTRONIK - Nixson Marisi.B; Indah Sari (YAYASAN PENDIDIKAN DAN PELAYANAN KESEHATAN RAHMAT HUSADA, 2025)
Electronic Evidence Documents have several provisions that can trigger various problems as evidence ranging from collection, storage, and preservation to authentication, validation, and application of electronic evidence, and raise questions about privacy, costs, ethics, and procedural management. The purpose of this study is to determine the procedures for submitting and examining documents, as well as the legal status of electronic documents as evidence in civil trials must comply with the provisions of Law No. 1 of 2024. The research method uses a normative juridical approach by analysing laws related to electronic documents as evidence. The results of the study state that the procedures for submitting and examining electronic documents as evidence in civil trials must comply with the provisions of Law No. 1 of 2024 and applicable procedural law, with the submission of electronic documents carried out directly or through an electronic litigation system in digital or printed format. After the document is submitted, it must be informed to the opposing party for examination and response, based on expert testimony if necessary to ensure the authenticity and integrity of the document during the trial process. Legally, electronic documents and their printouts have equal standing with conventional evidence as long as they meet authentication and relevance requirements and are protected from loss, theft, or unauthorized alteration through a registered electronic delivery service that provides proof of delivery and maintains document security. Numerous court decisions have recognized electronic documents as valid evidence, strengthening their position in the civil justice system as valid and effective instruments in line with technological developments and modern legal requirements.